Tradition and change in Maori leadership - Walker, Ranginui (Research Unit for Maori Education, University of Auckland, 1993)
Keywords: capitalism; colonisation; government; government relations; imperialism; kīngitanga; land loss; land theft; leadership; mana whenua; māori battalion; rangatira; urbanisation

'Te Wai-Kaukau o nga matua tipuna': myths, realities, and the determination of mana whenua in the Waikaremoana district. - Wiri, Robert K. J. (ResearchSpace@Auckland, 1994)
In the heart of the North Island of New Zealand lies a mountainous terrain called Te Urewera, the spiritual homeland of the Tϋhoe people. Hidden away in the southern portion of Te Urewera is Waikaremoana, a lake and a land with a history and tradition that are as fascinating as they are controversial. Waikaremoana is the 'tūrangawaewae' of the Ngāti Ruapani section of Tūhoe, and it is they and their lands that are the key focus of this M.A thesis. This thesis deals essentially with the concept of land ownership or mana whenua. It analyses the relationship between customary and colonial concepts of mana whenua in the Waikaremoana district, and examines the conflicting nature of these two different cultural concepts of the land and its history. In many ways this dissertation is unique, as it is a tribal history written by tangata whenua for tangata whenua. It allows today's tangata whenua to see their history through their predecessor's eyes and reawakens the past struggles of their ancestors. It gives tangata whenua a sense of dignity and pride in their heritage and traditions that give them their identity. 'Ko te uri o Tūhoe, moumou kai, moumou tāonga, moumou tangata ki te pō!'
Keywords: iwi; mana whenua; tino rangatiratanga